北極海における氷況把握のための画像解析法の開発─自動化した表面状態判別とその測定結果─ - 田中, 康弘; 舘山, 一孝; 高橋, 修平; 亀田, 貴雄; 榎本, 浩之 (公益社団法人日本雪氷学会, 2015)
メルトポンドは氷や雪より低いアルベドを持ち，日射吸収量が増加するとアイスアルベドフィード バックが進行する．本研究では北極航海観測で得られた船前方の氷況を撮影したカメラ画像から開放 水面，メルトポンド，海氷を検出する画像解析法を開発した．この手法ではまず，画像の明度ヒスト グラムを平滑化するためフーリエ領域におけるフィルタリングを行い，表面状態を3 つに分類した． 目視による表面状態の判別を真値としてこの結果と検討すると，高い正答率が得られたのはブラック マン窓を用いて遮断周波数を0.05 ならびにフィルタ長を51 とした低域通過フィルタであった．この 正答率は開放水面と海氷の一方が存在する1 ピークで89.5%，開放水面と海氷またはメルトポンドと 海氷の2 種類が混在する2ピークで80.5%，開放水面，メルトポンドと海氷の3種類が混在する3ピー クで64.0% であった．さらに，1 ピークでは明度の閾値，2 ピークでは赤および緑成分のヒストグラ ムの関係から表面状態をそれぞれ2 つに判別し，メルトポンドが存在する2 ピークの正答率は88.2% であった．以上の手法から航跡上の表面状態を自動的に把握することが可能になった．Because melt ponds have lower albedo than snow and ice, the ice albedo feedback process accelerates to increase the amount of solar absorption and sea ice melt. In this study, an automatic image analysis method is developed in order to detect open water, sea ice, and melt ponds using the forward looking camera images obtained from observations of the Arctic Ocean ice during summer and autumn. Comparing an automatic image analysis to visual observations of the images, we can detect melt ponds on the sea ice. First, this method performs filtering in the Fourier domain to smooth the brightness histogram of the image, and sea ice conditions are classified into three categories. The low pass filter (LPF) specifications for obtaining a high concordance rate were a cutoff frequency of 0.05 and a filter head of 51 using a Blackman window. Then, the concordance rate was 89.5% at one peak (for open water or sea ice only), 80.5% at two peaks (for open water and sea ice, or melt pond and sea ice), and 64.0% at three peaks (for open water, melt pond, and sea ice). Second, the surface conditions are classified into two types by using the brightness threshold at one peak, and making a relationship of the red and green histogram at two peaks. As a result, the concordance rate of two peaks achieved 88.2 %. Finally, our image analysis method automatically enabled surface condition distinctions on cruise tracks in the Arctic Ocean. journal article